Perceived Social Resources Affect Help-Seeking and Academic Outcomes in the Initial Phase of Undergraduate Studies - Schlusche, Christian; Schnaubert, Lenka; Bodemer, Daniel (Frontiers in Education, 2021)
First-year students are challenged cognitively and socially by the need to integrate into a new environment. This article investigates the role of peer students as a social resource for academic help-seeking to overcome knowledge-related difficulties. Receiving useful help may require close and regular contacts (social embeddedness) as well as awareness about peers’ knowledge (group awareness). Hence, effects of social embeddedness and group awareness on academic success (i.e., achievement, satisfaction, and dropout intention) are expected to be mediated by academic help-seeking. First-semester students in science (*n* = 49) and engineering (*n* = 80) have been surveyed. Both study programs differ in occasions to form small groups, which may influence students’ aggregation of social resources. Both social embeddedness (engineering only) and group awareness (both groups) predict successful academic help-seeking. Moreover, the effect of group awareness on student satisfaction and dropout intention is partially mediated by successful academic help-seeking (engineering only). Both social variables can contribute to help-seeking behavior and students’ academic success. The results provide evidence to advice researchers and practitioners to improve academic help-seeking among students.